La señorita Mapp - Benson, E. F. (Edward Frederic), 1867-1940; Vales, José C., 1965-; Benson, E. F. (Edward Frederic), 1867-1940. (Madrid : Impedimenta, 2013)
Miss Elizabeth Mapp, magnificent, grande dame and heiress, is always on the lookout lest her neighbors fall outside the bounds of perfect, exemplary manners. But her tightly controlled world is soon beset on all sides by interlopers, first in the disturbingly masculine form of two very different retired army officers, both of whom are anything but retiring in their conflicting aims upon her heart.
Online resource; title from ePub title page (Digitalia, viewed February 18, 2018)
Keywords: Mapp, Miss (Fictitious character) -- Fiction; Lucia (Fictitious character) -- Fiction; Women -- England -- Fiction; Female friendship -- Fiction; Humorous fiction; Electronic books